More iOS6 development : further explorations of the iOS SDK - Horovitz, Alex; Kim, Kevin; LaMarche, Jeff; Mark, David (Apress Imprint: Apress, 2013)
Interested in iPhone and iPad apps development? Want to learn more? Whether you're a self-taught iPhone and iPad apps development genius or have just made your way through the pages of Beginning iOS 6 Development, we have the perfect book for you. More iOS 6 Development: Further Explorations of the iOS SDK digs deeper into Apple's latest iOS 6 SDK. Bestselling authors Dave Mark, Alex Horovitz, Kevin Kim and Jeff LaMarche explain concepts as only they can-covering topics like Core Data, peer-to-peer networking using GameKit and network streams, working with data from the web, MapKit, in-application e-mail, and more. All the concepts and APIs are clearly presented with code snippets you can customize and use, as you like, in your own apps. If you are going to write a professional iPhone or iPad app, you'll want to get your arms around Core Data, and there's no better place to do so than in the pages of this book. The book continues right where Beginning iOS 6 Development leaves off, with a series of chapters devoted to Core Data, the standard for Apple persistence. Dave, Alex, Kevin and Jeff carefully step through each Core Data concept and show techniques and tips specifically for writing larger apps-offering a breadth of coverage you won't find anywhere else. The Core Data coverage alone is worth the price of admission. But there's so much more! More iOS 6 Development covers a variety of networking mechanisms, from GameKit's relatively simple BlueTooth peer-to-peer model, to the addition of Bonjour discovery and network streams, through the complexity of accessing files via the web. Dave, Alex, Kevin, and Jeff will also take you through coverage of concurrent programming and some advanced techniques for debugging your applications. The enhanced multitasking, threading, memory management and more are important. Apps are getting more and more complex, including sophisticated game apps that offer virtual or augmented reality experiences and new mapping views that take advantage of sensors and other APIs in the newest iOS 6 SDK. Whether you are a relative newcomer to iPhone and iPad or iOS development or an old hand looking to expand your horizons, there's something for everyone in More iOS 6 Development.